Exploring the Impact of Psychosocial Factors on the Integration of ICT in Teaching Electrical/Electronic Technology Education at Tertiary Level: A Case Study in North-West Nigeria - Ogbuanya, Chinyere Theresa (Universitas Negeri Padang, 2023)
This research investigates the psychosocial variables influencing lecturers' reluctance to utilize information and communication technology (ICT) in teaching electrical/electronic technology education (EETE) within tertiary institutions in North-West Nigeria. Utilizing a descriptive survey research design, the study focused on a sample of 87 lecturers across seven states in the region. A structured questionnaire, validated by three experts and with a Cronbach Alpha reliability value of 0.88, was employed for data collection. The findings, analyzed using mean, standard deviation, and Pearson correlation, revealed that competence in ICT and subject matter, attitude, motivation, environmental perception, peer group pressure, and school administration significantly impact lecturers' adoption of ICT tools in teaching. Moreover, gender, experience, and qualification were identified as additional factors influencing the use of ICT in teaching. The study recommends that state governments, particularly through their ministries of education, play a proactive role in promoting asynchronous/synchronous delivery systems for instructional planning, delivery, and evaluation to guide lecturers in tertiary institutions within the studied region.